The neutrophil extracellular trap-related gene FPR1 (formyl peptide receptor 1) as a potential prognostic and therapeutic target in osteosarcoma - Shihao Li; Qiong Yuan; Yuanyuan Zhang; Haiyang Zhang (BMC Musculoskeletal Disorders)
Abstract Background Neutrophil extracellular trap (NET) has been implicated in cancer progression and metastasis. Nevertheless, the role of the NET-related gene, formyl peptide receptor 1 (FPR1), in osteosarcoma (OS) remains largely unexplored. This study aimed to investigate the prognostic significance and biological function of FPR1 in OS. Methods The least absolute shrinkage and selection operator (LASSO) algorithm was employed to construct a NET-related prognostic model utilizing OS datasets from TARGET and GEO (GSE21257) databases. The scRNA-seq dataset GSE162454 was then used for verifying the role of NET-related model in OS at single-cell resolution. Next, survival analysis and multivariate cox regression analysis were performed to evaluate the prognostic value of FPR1 in OS patients. The CIBERSORT algorithm was conducted to evaluate the relationship between FPR1 levels and immune cell abundance. Subsequently, the biological role of FPR1 was explored through CCK-8, and transwell assays in OS cell lines. Results A signature NET score, comprising four NET-related genes (TNFRSF10C, FPR1, BST1 and SELPLG), was constructed to predict the prognosis of OS. The survival outcomes for patients in high-NET score group were markedly worse than that in the low-NET score group. Meanwhile, at single cell resolution, OS cells progressively evolved into tumors with elevated NET scores. Furthermore, FPR1 levels were markedly reduced in OS cells when compared to normal osteoblast cells, and the overexpression of FPR1 notably suppressed OS cell viability, migration and invasion. Additionally, OS patients exhibiting high levels of FPR1 demonstrated a favorable overall survival. Moreover, these patients also had a higher proportion of M1 macrophages and a lower proportion of M0 macrophages. Conclusion Collectively, our study indicates that the NET-related gene FPR1 is closely related to tumor progression, prognosis and immune infiltration in OS.